2016
DOI: 10.1259/dmfr.20150389
|View full text |Cite
|
Sign up to set email alerts
|

Fractal properties of the trabecular pattern of the mandible in chronic renal failure

Abstract: Objectives: The purpose of this study was to evaluate fractal analysis as a tool to quantitatively determine the mandibular trabecular bone changes in patients with chronic renal failure (CRF). Methods: In the present study, fractal analysis was performed using ImageJ (National Institutes of Health, Bethesda, MD) program with box-counting method over panoramic radiographs of 25 patients (14 females and 11 males) with CRF and 26 healthy individuals (14 females and 12 males) as a control group. The fractal dimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
32
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(43 citation statements)
references
References 30 publications
5
32
0
6
Order By: Relevance
“…Presently, fractal dimension was calculated by the box-counting method as published by White and Rudolph. 22 It has been demonstrated that this methodology is able to show differences in bone density on panoramic radiographs of patients with osteoporosis, 42 43 hyperparathyroidism, 44 sickle cell anemia, 45 chronic kidney disease, 46 and osteogenesis imperfecta. 47 Apparently, it is the first study using fractal analysis for characterization purposes in a mandibular case of OR.…”
Section: Discussionmentioning
confidence: 99%
“…Presently, fractal dimension was calculated by the box-counting method as published by White and Rudolph. 22 It has been demonstrated that this methodology is able to show differences in bone density on panoramic radiographs of patients with osteoporosis, 42 43 hyperparathyroidism, 44 sickle cell anemia, 45 chronic kidney disease, 46 and osteogenesis imperfecta. 47 Apparently, it is the first study using fractal analysis for characterization purposes in a mandibular case of OR.…”
Section: Discussionmentioning
confidence: 99%
“…48 Pothuaud et al 14 The present study adopted fractal analysis as a method for estimating mandibular trabecular texture since it represents a mathematical method useful for analysing complex structures such as the trabecular bone. 33,35 It is commonly used to describe the texture roughness and characterize the high degree of complexity of fractal objects by a repetition of self-similarity of the texture grey-level variations over different scales. 36,49 Although the Image J, a freely downloaded programme obtained from the National Institutes of Health, has been commonly selected as a software to calculate fractal dimension on panoramic radiographs, we processed the images by using MATLAB R2016a to customize a computer program for obtaining measures of fractal dimension, lacunarity and some trabecular architecture morphologic features in panoramic radiographs based on previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…20,21 Fractal analysis is a non-invasive imaging tool to obtain data regarding bone microarchitecture, and it has been used in several studies in the field of dentomaxillofacial radiology. [22][23][24][25][26][27][28][29] In endocrine pathologies, fractal analysis and other textural imaging tools (e.g., lacunarity and morphologic aspects) have been proposed to evaluate osteoporosis, 19,[30][31][32] osteogenesis imperfecta, 33 hyperparathyroidism, 34 chronic renal failure, 35 sickle cell anemia, 36 and diabetes mellitus. 37 To date, there are no published reports evaluating these parameters in panoramic radiographs of SSH individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Essa disparidade foi atribuída a diferenças nos locais anatômicos estudados e diferenças nos métodos usados para obter as Desde então, no campo da odontologia, a DF representa uma excelente ferramenta para estudar o padrão ósseo trabecular. Essa análise tem sido utilizada para o estudo de doenças que exibem alterações ósseas, doenças metabólicas e doenças que interferem na densidade óssea, como a osteoporose,83,92 talassemia maior,93 DM tipo 1 e 2,94 câncer de mama em terapia com inibidores de aromatase,95 osteogênese imperfeita em terapia com pamidronato 96 e IRC,97 por meio de radiografias periapicais, radiografias panorâmicas e tomografia computadorizada. simples e econômica para avaliação da estrutura óssea trabecular em indivíduos com IRC.…”
unclassified
“…Os resultados encontrados neste estudo podem ser justificados pela possível presença de DMO-IRC nos pacientes avaliados e apesar de não termos encontrado correlação entre os valores de cálcio total, fosfatase alcalina e PTH, acredita-se que o somatório desses fatores esteja diretamente relacionado a diferença significativamente menor da DF e IP no GE.Os menores aumentos da DF e IP podem também ser explicados pelas alterações trabeculares relacionadas à IRC, com diminuição no número e aumento de lacunas entre trabéculas, levando a diminuição na complexidade e densidade da estrutura. Essas alterações já foram verificadas no osso trabecular em análise da estrutura óssea por meio de microtomografia computadorizada e sua associação com a IRC 97. Assim, alterações como espessamento e reabsorção nas trabéculas,…”
unclassified